2008
DOI: 10.1677/joe-07-0639
|View full text |Cite
|
Sign up to set email alerts
|

Real-time analysis of gene regulation by glucocorticoid hormones

Abstract: There is increasing evidence that temporal factors are important in allowing cells to gain additional information from external factors, such as hormones and cytokines. We sought to discover how cell responses to glucocorticoids develop over time, and how the response kinetics vary according to ligand structure and concentration, and hence have developed a continuous gene transcription measurement system, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Glucocorticoids (GCs) are steroid hormones that regulate a range of biological functions essential for life, including normal homeostasis, glucose metabolism, resolution of inflammation and development (McMaster et al, 2008;Tu et al, 2018;Tanaka et al, 2017). GCs exert their biological effects through the ubiquitously expressed glucocorticoid receptor (GR; also known as NR3C1), a ligand-inducible transcription factor of the nuclear hormone receptor superfamily (Hollenberg et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids (GCs) are steroid hormones that regulate a range of biological functions essential for life, including normal homeostasis, glucose metabolism, resolution of inflammation and development (McMaster et al, 2008;Tu et al, 2018;Tanaka et al, 2017). GCs exert their biological effects through the ubiquitously expressed glucocorticoid receptor (GR; also known as NR3C1), a ligand-inducible transcription factor of the nuclear hormone receptor superfamily (Hollenberg et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…2011 ). In humans cortisol is the principal circulating Gc, but additional modulatory molecules are present including cortisone and the 5α-reduced cortisol metabolites ( McMaster et al . 2008 , Nixon et al .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, corticosteroids work by binding to glucocorticoid receptors, altering transcription of various genes either directly inducing transcription at the promotor region or by inactivating cofactors required for transcription of proinflammatory proteins 29 . One study concludes that this first step in gene transcription activity alone can take approximately 3 hrs from the time the glucocorticoid comes in contact with a cell 30 . It is well demonstrated that cytokines modulate cellular behavior and play a role in pain signaling and neuronal sensitization 31 .…”
Section: Discussionmentioning
confidence: 99%
“…29 One study concludes that this first step in gene transcription activity alone can take approximately 3 hrs from the time the glucocorticoid comes in contact with a cell. 30 It is well demonstrated that cytokines modulate cellular behavior and play a role in pain signaling and neuronal sensitization. 31 Thus, corticosteroid pain relief generally takes longer to begin, with the duration of pain relief measured in months.…”
Section: Time Until Relief From Corticosteroid Injectionmentioning
confidence: 99%